Effect of brand trust and commitment of a mobile wallet in Indonesia - PUTRA, H.D; ASTUTI, E.S; KUSUMAWATI, A.; ABDILLAH, Y. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The objective of this document is to analyze a trust brand model within the use of mobile wallets in Indonesia in 2020. 460 people were surveyed using the machine’s formula. The result of this search shows that; Brand confidence has a positive effect on brand engagement, with a significant path coefficient of 0.338, with P values of 0.002 <a significance level of 0.05. The study finding gives a new marketing idea, in understanding the reasons for the importance of the brand trust factor among the use of mobile wallet in Indonesia.